Pengamanan Gambar dengan Metode Cipher Block Chaining - Made Yayang Eka Prananda; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Data security is something that everyone needs to maintain their privacy, for example images. Images are very familiar to everyone, because we can capture various moments in the form of images. But there are some people who steal someone's image to misuse it for personal gain. Image pixel encryption using cryptography can be an alternative in securing the image. In this study, the cipher block chaining method is used to encrypt each pixel. The results of using this method are quite satisfactory, the resulting image becomes more abstract. The encrypted image can also be decrypted into the original image. However, the resulting pattern is still the same as the previous image pattern. So the use of this method may be more effective when combined with other cryptographic methods.